THE ANALYSIS OF LOCAL REVENUES AND THE AFFECTING FACTORS IN THE IMPLEMENTATION OF REGIONAL AUTONOMY IN ACEH PROVINCE - Rahmad Rahmad; T. Zulham; Chenny Seftarita (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2019)
Abstract This study aimed to determine the effect of population numbers, GRDP and inflation on local revenues. The model used was the OLS method using panel data. The results showed that the population had a positive and significant effect on the Local Revenue of regencies and cities t-test which showed that the population had  positive regression coefficient of 5.728641 and  significance value smaller than 0.05, that is equal to 0.0001. GRDP had  positive and significant effect on the local revenues of regencies and cities in Aceh. It can be seen in the results of the calculation of the t-test which showed that GRDP had positive regression coefficient of 4.473196 and significance value smaller than 0.05, that is equal to 0.0001, while inflation had a negative and significant effect on the local revenues of the regencies and cities. The regression coefficient value of -0.023161 that inflation had a negative effect on local revenues. If there is an increase in inflation of 1%, it will cause a decrease in local revenues of 0.023161%. Based on the 2-sided test on the individual parametric significant test on the inflation rate variable, The t-count value was smaller than the t-table which was -0.886238 and a significant value of 0.3905 0.05. The coefficient of determination or goodness of fit is obtained by a number of 0.888824. The contribution of all independent variables in explaining the dependent variable is 88.8 percent. The remaining 11.2 percent is explained by other variables outside this research model.